PENGARUH MEKANISME TATA KELOLA PERUSAHAAN, RISIKO KEUANGAN, DAN STRUKTUR KEPEMILIKAN TERHADAP MANAJEMEN LABA - Sasmito Widi Nugroho (STIE Mandala Jember, 2017)
This study aims to analyze the influence of corporate governance mechanisms, financial risk, and ownership structure on earnings management. Proxy for good corporate governance mechanism is Managerial ownership, institutional ownership, independent commissioner and independent audit committee. Proksi for the financial risk is leverage ratio, free cash flow, and the current ratio. Earnings management is measured by discretionary accruals using the model of Kang Sivaramakrishnan. The sample of this research is 27 companies in the manufacturing sector which were listed in Indonesian Stock Exchange in 2010-2012. The results shows that institutional ownership, independent commissioner, independent audit committee have no effect on earnings management. Managerial ownership and leverage ratio has a positive effect on earnings management. Free cash flow, current ratio and ownership structure has a negative effect on earnings management.